Estimates for stability of the Runge-Kutta method for differential equations with a variable operator - Bakaev , N. Yu. (Ukrains’kyi Matematychnyi Zhurnal, 2025)
Questions of stability of difference schemes approximating differential equations with varying operator in a Banach space constructed by the Runge-Kutta method are studied.